Religiosidade dos profissionais de saúde que atuam na linha de frente da pandemia de covid-19 - Couto, Manuela da Silva (2022)
The present study aimed to evaluate the religiosity of health professionals who work on the front lines of the Covid-19 pandemic. The search had a quantitative, descriptive, analytical and transversal approach. The study population consisted of health professionals (nurses, technicians, physiotherapists and doctors) who worked directly on the front line of nursing patients with Covid-19. Data collection was carried out online and through the Google Forms tool using a structured questionnaire containing sociodemographic data, chronic diseases, medications and information about work in the face of Covid-19. To assess religiosity, the Duke Religiosity Scale - DUREL was used. The sample consists of 100 health professionals, with a mean age of 33.3±8.3 years, most of them female (81.0%), with a higher percentage of nursing technicians (41.0%) and nurses (39.0%). Regarding the Duke Religiosity scale DUREL, the subscale corresponding to organizational religiosity computed a median of 4 points, considered low religiosity; the non-organizational religiosity subscale computed 3.5 points, defined as high; and intrinsic religiosity, 6 points, considered high. The results of the study showed that health professionals working on the front lines of Covid-19 had low organizational religiosity (public religious practices), non-organizational religiosity (private religious activities such as prayer) and intrinsic religiosity (religious commitment or religious motivation) high.